PERAN SISTEM INFORMASI MANAJEMEN DALAM MENINGKATKAN LOYALITAS BRAND DI KALANGAN GENERASI Z - Cut Nadhira Shahnaz; Muhammad Irwan Padli Nasution (INTERNATIONAL, Journal of Sharia Business Management, 2025)
Generation Z as a digitally native consumer group, possesses unique behavioral patterns and expectations that require companies to adopt innovative and adaptive approaches in building brand loyalty. Unlike previous generations, Generation Z places high value on personalization, convenience, digital engagement, and authenticity when interacting with brands. In this context, management information systems play a critical role in enabling companies to collect, process, and analyze real-time consumer data, which can then be used to formulate targeted and meaningful marketing strategies. This study employs a literature review method to analyze how management information systems support efforts to increase brand loyalty among Generation Z. The findings indicate that an effective implementation of management information systems allows companies to deliver personalized customer experiences, maintain responsive two-way communication, and provide seamless digital services aligned with Generation Z's expectations. Key system components such as customer relationship management (CRM), data analytics tools, artificial intelligence–based recommendation systems, and integrated digital platforms are essential in fostering long-term engagement with younger consumers. Overall, companies that successfully optimize management information systems can create higher perceived value, leading to increased trust, emotional connection, and stronger consumer commitment toward a brand.